Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jcb.28879
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐202 inhibits cell proliferation, invasion, and migration in breast cancer by targeting ROCK1 gene

Abstract: Purpose The aim of this study was to research the effect of miR‐202 on breast cancer cells proliferation, invasion, and migration. Methods TCGA analysis was used to research miR‐202 expression and overall survival in patients with breast cancer. Transfection with miR‐202 mimics or cotransfection with miR‐202 mimics and ROCK1 expression vector was performed on breast cancer cells. Reverse transcription polymerase chain reaction was used to detect the miR‐202 expression of breast cancer tissues and cells. Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ). In addition, miR-202 has been previous shown to exert suppressive roles on the invasive and migratory capacities of tumor cells ( 43 - 45 ). According to the aforementioned findings from the present and previous studies, it could be hypothesized that miR-202 can regulate EMS progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ). In addition, miR-202 has been previous shown to exert suppressive roles on the invasive and migratory capacities of tumor cells ( 43 - 45 ). According to the aforementioned findings from the present and previous studies, it could be hypothesized that miR-202 can regulate EMS progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-202 mediates suppressive invasive roles in various types of human tumors ( 21 , 44 ). Xu et al ( 45 ) reported that miR-202 targeted Rho-associated protein kinase 1 to inhibit the invasive and migratory abilities of breast cancer. In addition, Zhang et al ( 18 ) found that miR-202 upregulation resulted in significant reductions in the migration and invasion of prostate cancer cells by targeting the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-202 is associated with several types of cancers such as ovarian cancer [12], lung cancer [13], and colorectal cancer [14]. miR-202 has been reported to have either a tumor-suppressive or oncogenic function (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Breast cancer blood up metastasis, poor survival outcome - [24] This discrepancy is presumed to be the result of differences in the sample processing methods, type of samples, detection methods, and characteristics of the recruited study groups.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was highly expressed in the drug-resistant breast cancer tissues [25]. However, some studies reported that it was downregulated in breast cancer cells and inhibited the tumorigenesis of breast cancer [27,28]. Although miR-202 has been studied for its function or expression in breast cancer, little is known about its potential diagnostic value in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The particular miRNAs in this paper are associated with cancer occurrence, metastasis and invasion. Indeed, miR-145, miR-202 and miR-374 has been proposed as diagnostic, prognostic or therapeutic marker of BLCA [45,46] .miR-202 and miR-347 participate in invasion, metastasis and cancer progression [46,47], while miR-145 modulates suppressor of cytokine signaling 7 (socs7) to enhance IFN-β expression, thus contributing to BLCA apoptosis. We speculate that deregulation of these miRNAs would be in consistence with the phenotype of POLR2K overexpression in BLCA, which should be further veri ed by experiments.…”
Section: Discussionmentioning
confidence: 99%